Thinking Skills in Practice: A Case Study of an English Curriculum at a Thai University - Kanokpermpoon, Monthon (LEARN Journal: Language Education and Acquisition Research Network, 2019)
Critical thinking is an important 21st century learning skill. In practice, how it is integrated into the curriculum is still in question, especially in a language curriculum, where its aim is to develop learners’ proficiency. In the context of Thailand, educational reform has led to a revised curriculum and Thai universities have responded to this. In one such university, a case study analysed a language curriculum and learning materials to determine the extent to which thinking skills were infused within them. The theoretical frameworks used in the analysis were the revised Bloom’s taxonomy and an active learning model. Low-level thinking skills were found to be dominant factors in the language curriculum when the revised Bloom’s taxonomy was used. However, active learning was seen to promote higher order thinking in the language curriculum. The suggested way to integrate thinking within the language curriculum is thus to embed a thinking skills framework and active learning in the curriculum design and learning materials.